The Aghlabids and their neighbours : art and material culture in 9th-century North Africa - Anderson, Glaire D.; Fenwick, Corisande.; Rosser-Owen, Mariam.; Lamine, Sihem. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2018)
The first dynasty to mint gold dinars outside of the Abbasid heartlands, the Aghlabid (r. 800-909) reign in North Africa has largely been neglected in the scholarship of recent decades, despite the canonical status of its monuments and artworks in early Islamic art history. The Aghlabids and their Neighbors focuses new attention on this key dynasty. The essays in this volume, produced by an international group of specialists in history, art and architectural history, archaeology, and numismatics, illuminate the Aghlabid dynasty's interactions with neighbors in the western Mediterranean and its rivals and allies elsewhere, providing a state of the question on early medieval North Africa and revealing the centrality of the dynasty and the region to global economic and political networks.